Who are we becoming? A critical, communicative, reflective, transformative, timely inquiry into the coming-to-be of adult education in the early 21st century - Aliki Nicolaides; Dominique T. Chlup; Robin Redmon Wright; Joellen E. Coryell; Dianne Ramdeholl; Thomas D. Cox (Adult Education Research Conference, 2012)
The perspectives included in this collaborative document reflect the authors‘ initial inquiry to explore who are we becoming as adult educators. We present five unique points of view that our role as adult educators holds potential to help adults seek ways into their own deep inquiries of what are true, beautiful, and just ways of life. Our inquiries give expression to how might we create conditions for truth, beauty, and justice to emerge in our communities, in the systems that we work in, that govern us and that make way for our individual collective humanity? The time is ripe to ask what are the diverse structures, systems and expressions of an evolving humanity where justice, grace, beauty and truth take new shapes to meet unseen demands placed on adults around the world and what role adult education will play.